Analisis Faktor-Faktor yang Mempengaruhi Minat Mahasiswa Akuntansi Berkarir Menjadi Akuntan Publik - Devi Naibaho; Poniman (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Abstract This research aims to determine the factors that influence accounting students interest in choosing a career as a public accountant. The sample taken in this research was 100 Accounting Students in the city of Batam using the Slovin formula with a significance level of 10%. The data collection technique in this research is by distributing questionnaires via Google Form which is measured using a Likert scale, and the data is processed using a statistical program in the form of IBM SPSS Version 26. The data analysis methods used in this research, namely descriptive statistical tests, data quality tests, classical assumption tests, multiple linear regression tests, coefficient of determination tests, and hypothesis tests consisting of t tests and f tests. The results of hypothesis testing in this study show that in particular professional training, job market considerations, personality and work environment have a positive and significant effect on accounting students interest in choosing a career as a public accountant. The coefficient of determination test result in this study was 0.394, so the independent variable in this study had an influence on the dependent variable of 60,6%, the remaining 39,4% was influenced by other variables outside this study. Keywords : Professional Training, Personality, Job Market Considerations Student, Personality, Work Environment, Student Interests